A bioreducible N-oxide-based probe for photoacoustic imaging of hypoxia. Issue 1 (December 2017) - Knox, Hailey; Hedhli, Jamila; Kim, Tae Wook; Khalili, Kian; Dobrucki, Lawrence; Chan, Jefferson
Abstract Hypoxia occurs when limited oxygen supply impairs physiological functions and is a pathological hallmark of many diseases including cancer and ischemia. Thus, detection of hypoxia can guide treatment planning and serve as a predictor of patient prognosis. Unfortunately, current methods suffer from invasiveness, poor resolution and low specificity. To address these limitations, we present Hypoxia Probe 1 (HyP-1), a hypoxia-responsive agent for photoacoustic imaging. This emerging modality converts safe, non-ionizing light to ultrasound waves, enabling acquisition of high-resolution 3D images in deep tissue. HyP-1 features anN -oxide trigger that is reduced in the absence of oxygen by heme proteins such as CYP450 enzymes. Reduction of HyP-1 produces a spectrally distinct product, facilitating identification via photoacoustic imaging. HyP-1 exhibits selectivity for hypoxic activation in vitro, in living cells, and in multiple disease models in vivo. HyP-1 is also compatible with NIR fluorescence imaging, establishing its versatility as a multimodal imaging agent. Hypoxia is a hallmark of many diseases including cancer and ischemia, and detection can be invasive and of low resolution and specificity. Here the authors show a hypoxia probe that converts non-ionizing light to ultrasound, which enables the acquisition of high-resolution 3D images in deep tissue.